The effect of business strategies on financial performance – An applied study on Saudi joint stock companies – - Alzahran, Tariq Hassan (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the impact of business strategies on financial performance in Saudi joint stock companies, and used the descriptive analytical method, and the study community is of all the industrial companies listed on the Saudi capital market and the 81 companies, and the sample of the study became after excluding companies whose data are not available during the study period (73) companies. Corporate financial reports were collected from 2010 to 2019, and the data was analysed using Panel data, based on the statistical method represented in the Multi- Regression. The comprehensive survey method of industrial companies in Saudi Arabia was used, and the study found that there was no impact of the product differentiation strategy on the financial performance of Saudi industrial companies, and that there was no impact of the cost leadership strategy on the financial performance of Saudi industrial companies. The size of the company also has a positive impact on the rate of return on ownership, leverage negatively affects financial performance, and the company’s life has a negative impact on financial performance. The study recommends future studies to increase the size of the sample and study all Saudi companies to ascertain the impact of business strategies on the performance of companies, and recommended companies to reduce indebtedness and leverage, so that the strategies provided by serving companies in raising financial performance, and working on the application of strategies in a scientific manner so that they have a positive impact on the performance of companies.